Participatory evaluation of ethno-veterinary livestock health practices by farmers from surrounding villages in Ranthambore Tiger Reserve, India - Meena, Deepak Chand; Meena, B.S.; Garai, Sanchita; Sankhala, Gopal (Indian Journal of Dairy Science, 2023)
The present study was conducted to document the ethno-veterinary practices, 360 livestock farmers from the 30 villages surrounding the tiger reserve were interviewed using an open-ended interview schedule to enlist all the practices against the ailments of livestock from the purposefully chosen zone namely Critical Tiger Habitat and buffer zone of the tiger reserve. For participatory assessment of the identified ethno-veterinary practices, Quantification of Indigenous Knowledge and to identify the best practices among over all practices one way variance followed by DMRT method were applied. Use of Drimia indica (Roxb.) Jessop was found most effective practice against the mastitis and use of seeds of Sorghum halepense L. against the diarrhoea, stem bark of Salodora persica L. for fever, and fruits of Areca catechu for treatment of prolapse in the livestock were found most effective practices. The pharmacodynamics of these ethno-veterinary techniques could therefore be studied before further replication and implementation.